2014
DOI: 10.5301/ejo.5000385
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Outcome of Ranibizumab for Neovascular Age-Related Macular Degeneration: A Thorough Analysis in a Real-World Clinical Setting

Abstract: Our results compare unfavorably with those of controlled trials. Treatment and follow-up regimens in real-world settings seem to have a major role in determining outcome. Lower age and BCVA at baseline were associated with better response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
1
10
3
1
Order By: Relevance
“…The CATT 6 and GEFAL 17 considered a difference of five EDTRS letters to represent noninferiority, whereas the MANTA 18 considered a difference of seven letters to be noninferior. 18 Because of the 'ceiling effect', whereby eyes starting treatment with good VA have little room for further improvement, many measures are dependent on the starting VA. 11,12,20 Adjusting for age, starting VA, number of injections, and visits reduced, but did not eliminate the significant variation between centres, suggesting there are other unmeasured factors that contribute to these variations in outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CATT 6 and GEFAL 17 considered a difference of five EDTRS letters to represent noninferiority, whereas the MANTA 18 considered a difference of seven letters to be noninferior. 18 Because of the 'ceiling effect', whereby eyes starting treatment with good VA have little room for further improvement, many measures are dependent on the starting VA. 11,12,20 Adjusting for age, starting VA, number of injections, and visits reduced, but did not eliminate the significant variation between centres, suggesting there are other unmeasured factors that contribute to these variations in outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] We have previously reported longitudinal results from a cohort of patients recruited from hospitals in the UK. 10,11,14 Patients had standardised data recorded at the point of care into an electronic medical record (EMR) system, and the grouped national findings showed that PRN retreatment after three loading doses resulted in moderately stable vision.…”
Section: Introductionmentioning
confidence: 99%
“…29 Two studies reported a decline in visual outcomes with the largest decline in VA of 2.0 letters. 30 In the remaining four studies the VA at study end remained similar to baseline values (−0.8 to 0.97 letters).…”
Section: Change In Vamentioning
confidence: 69%
“…[19][20][21] This has been previously reported and is attributed to the difficulties in complying with strict follow-up criteria of the trials. 27,28 However, the fundamental aspect of our results was the significant visual acuity gain obtained from phacoemulsification.…”
Section: -11mentioning
confidence: 90%